2020
DOI: 10.15414/jmbfs.2020.10.1.42-48
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Chemical Composition of the Essential Oil of Origanum Compactum From the Seven Regions of Morocco and Their Antimicrobial Activity

Abstract: The aim of this work is to determine the chemical composition of the essential oil of Origanum compactum, from the region of Meknes (Morocco), and their antimicrobial effect, and on the other hand, to carry out a comparison between the chemical composition of this essential oil with the six regions of Morocco: Larache, Chefchaouen, Al Hoceïma, Tetouan, Taounate and Rabat. The essential oils of Origanum compactum thus obtained were analyzed and identified by gas chromatography coupled with mass spectrometry (GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…EO yield of O. majorana varied from 0.04 to 0.09% during the full-flowering stage in Tunisia [ 26 ]. O. compactum average yield was about 3.62% from the region of Meknes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EO yield of O. majorana varied from 0.04 to 0.09% during the full-flowering stage in Tunisia [ 26 ]. O. compactum average yield was about 3.62% from the region of Meknes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that carvacrol, a phenolic compound, possesses high levels of antimicrobial activity. While EOs from other Origanum species showed to possess high levels of antimicrobial activity, the EO inhibited the growth of all of the tested microbial strains [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced in several works, carvacrol and thymol as well as their biosynthetic precursors, such as cymene and γ-terpinene, represent a major part of total oil components (more than 70%) [34,36,37]. Moreover, β-caryophyllene and caryophyllene oxide were also observed in significant amounts [25,38,39]. Therefore, the chemical composition may be related to biosynthetic pathways, promoting the overexpression of some components and blocking the synthesis of others [40,41].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Essential oil (with carvacrol and/or thymol, linalool, γ-terpinene, and pcymene), polyphenols (flavonoids and phenolic acids), triterpenoids, and sterols (Bhargava et al, 2015;Chishti et al, 2013;De Falco et al, 2013;El Babili et al, 2011;Fliou et al, 2020;Gutiérrez-del-Río et al, 2018;Hernández-Hernández et al, 2014;Koldaş et al, 2015;Lombrea et al, 2020;Lukas et al, 2015;Moghrovyan et al, 2019;Oniga et al, 2018;Parra et al, 2021;Pezzani et al, 2017;Pitaro et al, 2013;Potente et al, 2020;Prakash et al, 2021;Scalas et al, 2018;Soltani et al, 2021;Teixeira et al, 2013;Węglarz et al, 2020;Zhang et al, 2014) Portulaca oleracea L.-Portulaca + + Ascorbic acid, a-tocopherols, omega-3 fatty acids, apigenin, gallotannins, quercetin, and kaempferol, alkaloids, terpenoids, flavonoids, and organic acids (Alam et al, 2014;Banerjee & Mukherjee, 2002;Fernández-Poyatos et al, 2021;Gatea et al, 2017;Iranshahy et al, 2017;Rahimi et al, 2019;Sicari et al, 2018;Siriamornpun & Suttajit, 2010;Zhou et al, 2015) Thymus L.-Thyme + + + Phenolic acids and flavonoids, caffeic, rosmarinic, p-coumaric acids, luteolin 7-O-glucoside, naringenin, and (−)-epicatechin, carvacrol, thymol, γ-terpinene, p-cymene, linalool, and phenols (Ateeq- Ur-Rehman et al, 2009;Bogavac et al, 2015;Dauqan & Abdullah, 2017;De Martino et al, 2009;…”
Section: Con Clus Ionmentioning
confidence: 99%